A preliminary study on sustainable approach for the Malay traditional food wrapping / Muhammad Nor Razin Mhd Nor, Shahrel Nizar Baharom and Nur Huzeima Mohd Hussain - Mhd Nor, Muhammad Nor Razin; Baharom, Shahrel Nizar; Mohd Hussain, Nur Huzeima (2021)
Malay food has tangled in changes of their wrapping practices. The use of plastic as wrapping has replaced leaves-wrapping practice which has been passed down from generations. This change is believed to bring a negative long-term effect to our health and environment. This paper presents an ongoing study to investigate the sustainable approach for the Malay traditional food wrapping. This study focused on current Malay traditional food wrapping practices and factors of changes in Malay traditional food wrapping practices. Quantitative approach was employed by using Pearson correlation and multiple regression data analysis to study the phenomenon. Collected data and findings of this research will help Malay traditional food producers to apply sustainable approach in wrapping practices of Malay traditional food wrapping.